2015
DOI: 10.1016/j.vaccine.2013.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant system AS02V enhances humoral and cellular immune responses to pneumococcal protein PhtD vaccine in healthy young and older adults: Randomised, controlled trials

Abstract: The improved immune response to PhtD vaccine containing the AS02V adjuvant system in comparison to alum suggests that the reduced immune response to vaccines in older adults can be partially restored to the response level observed in young adults. ClinicalTrials.gov identifiers: NCT00307528/NCT01767402.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…In the groups that received vaccines containing the AS02 V adjuvant system, there was a trend toward a higher incidence of solicited local (any and grade 3) AEs and of specific solicited general AEs (fatigue and myalgia) compared to with the groups that received vaccines containing alum or the control 23PPV vaccine. Previous studies of adults Ն65 years of age and younger adults administered PhtD vaccines reported a tendency toward higher reactogenicity with AS02 V -than with alum-containing formulations (27). An increase in reactogenicity was also observed in a study of a vaccine containing PhtD, dPly, and protein D administered with the AS03 adjuvant system compared to with antigen alone (28).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In the groups that received vaccines containing the AS02 V adjuvant system, there was a trend toward a higher incidence of solicited local (any and grade 3) AEs and of specific solicited general AEs (fatigue and myalgia) compared to with the groups that received vaccines containing alum or the control 23PPV vaccine. Previous studies of adults Ն65 years of age and younger adults administered PhtD vaccines reported a tendency toward higher reactogenicity with AS02 V -than with alum-containing formulations (27). An increase in reactogenicity was also observed in a study of a vaccine containing PhtD, dPly, and protein D administered with the AS03 adjuvant system compared to with antigen alone (28).…”
Section: Discussionmentioning
confidence: 71%
“…The observation of enhanced IgG responses with AS02 V compared to with the alum adjuvant was consistent with studies of other vaccines using MPL-and QS-21-containing adjuvant systems (39), including the previous study on TABLE 2 Percentage of subjects reporting unsolicited adverse events during the 31-day postvaccination period (total vaccinated cohort) AE group % (95% confidence interval) of subjects reporting unsolicited AEs for the indicated vaccination group (n) PhtD-dPly10/AS02 V (23) PhtD-dPly10/alum (24) PhtD-dPly30/AS02 V (24) PhtD-dPly30/alum (24) 8PCV/AS02 V (24) 8PCV/alum (23) 23PPV ( PhtD vaccination in elderly adults (27). Anti-PhtD and anti-Ply antibody responses were also observed in the groups administered 8PCV, which contained 22 g PhtD and 15 g dPly as protein conjugates for two serotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. 164 In the absence of adjuvant, the production of antibodies to PhtD was found to be higher in the younger group in the setting of acceptable safety and tolerability, while inclusion of adjuvant was associated with comparable antibody responses in both groups. Inclusion of ASO2v was also 29 associated with increased efficiency of PhtD-specific cell-mediated immune responses in both groups measured according to the frequency of circulating anti-specific CD4 + T cells.…”
Section: Pspa-based Vaccinesmentioning
confidence: 85%
“…Inclusion of ASO2v was also 29 associated with increased efficiency of PhtD-specific cell-mediated immune responses in both groups measured according to the frequency of circulating anti-specific CD4 + T cells. 164 On a cautionary note, it has recently been reported that truncated derivatives of PhtD are more effective vaccine antigens than the full-length protein when tested in mice. 165 However, the relevance of these findings to vaccine efficacy in humans has not been established.…”
Section: Pspa-based Vaccinesmentioning
confidence: 99%